CLINICAL STUDY OF EFFECT OF MUNDI TAILAM ON AKALAPALITHYAM WITH NASYAKARMA AND NASYA WITH PANAKARMA - Anuradha, Devulapally (Journal of Drug Delivery and Therapeutics, 2012)
Healthy hair is indication of healthy life. Akalapalithyam i.e. premature greying of hair is common burning problem particularly in youth resulting in cosmetic, mental and social issue. It is mainly due to pollution, modern life, malnutrition, physical & mental stress and hereditary factors. Several products such as hair oils, dyes etc. are available in the market claiming cure for Akalapalithyam. Most of the dyes have side effects and complications. The need of the hour is to evolve a safe & effective cure for this growing problem. Administration of medicine through nose is nasya. This technique is useful in preventing as well as curing this disease. It expels disease causing agents.Â Nasa (Nose) is an entrance of Siras (Head). Therefore the nasya karma is the first choice of treatment to Sirokapala roga. The present clinical study is to evaluate the role of only Nasyakarma (Nasal Drops) and Nasyakarma with Panakarma (oil intake) of Munditailam on Premature greying (Akalapalithyam). In the present study 30 patients suffering from Akalapalithyam were randomly selected and divided into two groups. Group -A - 15 patients were given only Munditaila nasyam. Group-B-15 patients were given both nasyam & Panam of Munditailam. The duration of treatment was 45 days. Response to the treatment was evaluated once in 15 days. The analysis is based on subjective improvement. Both the groups had good relief but group B showed significant improvement over group A. Keywords: Munditailam, Premature greying (Akalapalithyam), Nasyakarma and Panakarma. Â